2017
DOI: 10.1038/srep44523
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic modelling of deep magmatic controls on porphyry copper deposit endowment

Abstract: Porphyry deposits, our main source of copper and of significant amounts of Mo, Re and Au, form at convergent margins in association with intermediate-felsic magmas. Although it is accepted that copper is transported and precipitated by fluids released by these magmas, the magmatic processes leading to the formation of economic deposits remain elusive. Here we perform Monte Carlo petrological and geochemical modelling to quantitatively link crustal magmatic processes and the geochemical signatures of magmas (i.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
133
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 140 publications
(141 citation statements)
references
References 43 publications
7
133
0
1
Order By: Relevance
“…Various Miocene large Cu-Mo±Au porphyry deposits (e.g., Junin/Llurimagua Cu-Mo deposit and the Cascabel thickness ranging from 50 to 70 km (Feininger andSeguin, 1983, Guillier et al, 2001). Such features are similar to those of magmatic systems typically associated with large porphyry Cu deposits (Loucks, 2014, Chiaradia andCaricchi, 2017) and the temporal and spatial proximity of Miocene deposits to the Quaternary arc rocks investigated lend support to the possibility that processes leading to the formation of porphyry type deposits under 370 the Quaternary arc of Ecuador could be currently ongoing. Therefore, the Quaternary arc rocks of Ecuador can be used as a proxy of a potentially fertile typical Andean subduction-related magmatic environment.…”
Section: Comparison With Ecuadorsupporting
confidence: 59%
“…Various Miocene large Cu-Mo±Au porphyry deposits (e.g., Junin/Llurimagua Cu-Mo deposit and the Cascabel thickness ranging from 50 to 70 km (Feininger andSeguin, 1983, Guillier et al, 2001). Such features are similar to those of magmatic systems typically associated with large porphyry Cu deposits (Loucks, 2014, Chiaradia andCaricchi, 2017) and the temporal and spatial proximity of Miocene deposits to the Quaternary arc rocks investigated lend support to the possibility that processes leading to the formation of porphyry type deposits under 370 the Quaternary arc of Ecuador could be currently ongoing. Therefore, the Quaternary arc rocks of Ecuador can be used as a proxy of a potentially fertile typical Andean subduction-related magmatic environment.…”
Section: Comparison With Ecuadorsupporting
confidence: 59%
“…During extensive fractionation of hydrous magmas in the lower crust, amphibole (±garnet) is stabilized in the fractionating assemblage and plagioclase is suppressed (Müntener et al, 2001), resulting in melts with elevated Sr, an absence of strong negative Eu anomalies (both elements being compatible in plagioclase), and depleted Y (compatible in amphibole and garnet). Such magma evolution is promoted in strongly compressional, thickened arc crust and is commonly associated with porphyry Cu ore deposits because impeded magma ascent from the lower crust facilitates volatile accumulation and enrichment in ore-forming components (Chiaradia, 2015;Chiaradia and Caricchi, 2017). The high Sr/Y values that result can be used to provide insights into arc magma evolution (Macpherson et al, 2006;Rodriguez et al, 2007), evaluate whether a magmatic system has the potential to form a porphyry-related ore deposit in exploration (i.e., is "metallogenically fertile"; Richards, 2011;Loucks, 2014) and track crustal thickness (Chapman et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Recent precise geochronological studies of porphyry deposits worldwide have indicated that deposits may form within tens of thousands of years (e.g., Henry et al, 1997;Shinohara and Hedenquist, 1997;Pollard et al, 2005;von Quadt et al, 2011;Chiaradia et al, 2013;Buret et al, 2016Buret et al, , 2017 or several million years (e.g., Ballard et al, 2001;Maksaev et al, 2006;Harris et al, 2008;Sillitoe and Mortensen, 2010;Barra et al, 2013;Deckart et al, 2013, 2014, andreferences therein;Leng et al, 2013). These longlived magmatic-hydrothermal events are typically attributed to episodic buildup and evolution of the underlying more voluminous pluton that feeds the upper crustal porphyritic intrusive complex (e.g., Sillitoe, 2010;Sillitoe and Mortensen, 2010;Chelle-Michou et al, 2014;Chiaradia and Caricchi, 2017;Leng et al, 2018).…”
Section: Formation and Duration Of The Pulang Porphyry Systemmentioning
confidence: 99%